2020
DOI: 10.1038/s42005-020-0359-6
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between graphs and networks

Abstract: Network science has become a powerful tool to describe the structure and dynamics of real-world complex physical, biological, social, and technological systems. Largely built on empirical observations to tackle heterogeneous, temporal, and adaptive patterns of interactions, its intuitive and flexible nature has contributed to the popularity of the field. With pioneering work on the evolution of random graphs, graph theory is often cited as the mathematical foundation of network science. Despite this narrative,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…a) Basic graph-based paradigm: Basic graph-based paradigm is based on the graph theory and it can be seen as a set of selection principles for microscopic laws of behaviour in network science [183] which typically involves a simplified graph representation and analysis of networks just concerned with nodes and their connections, e.g. [184], [185].…”
Section: B How To Generate Network Using Different Modelling Paradigmsmentioning
confidence: 99%
See 1 more Smart Citation
“…a) Basic graph-based paradigm: Basic graph-based paradigm is based on the graph theory and it can be seen as a set of selection principles for microscopic laws of behaviour in network science [183] which typically involves a simplified graph representation and analysis of networks just concerned with nodes and their connections, e.g. [184], [185].…”
Section: B How To Generate Network Using Different Modelling Paradigmsmentioning
confidence: 99%
“…Graph theory began when, in 1735, Leonhard Euler presented the first mathematical demonstration based on geometry of position to solve the seven bridges of Köningsberg puzzle [186], [187]. Graph theory focuses on providing rigorous proofs for graph properties, such as graph enumeration, coloring, and covering [183], [188], while the evolution of random graphs motivated graph theory to generate a new branch of network science for a separate direction: quantifying the structure and dynamics of real-world complex systems [183].…”
Section: B How To Generate Network Using Different Modelling Paradigmsmentioning
confidence: 99%
“…A whole population network includes all individuals within a population, irrespective of their participation in specific layers, so unconnected nodes are included too. The result is a diffuse network without nodes with high centrality [9].…”
Section: Descriptive Statistics Of the Networkmentioning
confidence: 99%
“…Recently, Robust Networks (RobNets) investigated the patterns of ANN architectures that were resilient to adversarial attacks and found that densely connected patterns resulted in improved robustness [27]. However, most real-world networks are not dense but sparse, with relatively few edges between nodes [28].…”
Section: Related Workmentioning
confidence: 99%